Strategy Head School in Increase Productivity Teacher SMK N 1 Muaro Jambi - Aripa, Aripa; Verdianto, Verdianto; Rahman, KA (FKIP Universitas Jambi, 2024)
This research aims to find out the strategies carried out by Vocational School Principals Negeri 1 Muaro Jambi in increasing teacher productivity at the school. Study This will be held in June 2024, at SMK Negeri 1 Muaro Regency Jambi Jambi Province. In In this research, the author uses qualitative research with a descriptive approach, namely the author goes directly into the field. In deciding In the sample, there are two techniques for determining informants, namely the Nonprobability Sampling technique, namely consists of Snowball Sampling and Purposive Sampling. The type of data used is primary and secondary data. Data collection techniques using interviews, observation and documentation. The research results show that the strategy carried out by the Head of Vocational Schools Negeri 1 Muaro Jambi has been carried out to increase teacher productivity in schools the. In between Which has done is increase discipline Teacher And give motivation and appreciation Work for para Teacher.